1995
DOI: 10.3382/ps.0740937
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter spp. in Broilers on the Farm and After Transport

Abstract: Colonization of the ceca and contamination on carcasses of chickens by Campylobacter spp. was investigated. Samples were taken on the farm and after transport and holding. In the first set of experiments, 20 chickens, obtained from each of 10 broiler farms, were collected from houses containing 6- to 7-wk-old birds. Half of the birds were slaughtered at the farm; the other half were transported (10 birds per chicken coop) to a holding facility and killed within 16 to 18 h. The levels of Campylobacter spp. on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
83
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(86 citation statements)
references
References 14 publications
1
83
0
1
Order By: Relevance
“…jejuni. They can be found on the carcasses of oven-ready ducks and duck products due to cross contamination by faecal matter from infected birds in the processing plant (Kasrazadeh and Genigeorgis 1987;Bryan and Doyle 1995;Stern et al 1995). Prescott and Bruin-Mosch (1981) examined 94 commercially reared ducks and found 88% carrying C. jejuni subsp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…jejuni. They can be found on the carcasses of oven-ready ducks and duck products due to cross contamination by faecal matter from infected birds in the processing plant (Kasrazadeh and Genigeorgis 1987;Bryan and Doyle 1995;Stern et al 1995). Prescott and Bruin-Mosch (1981) examined 94 commercially reared ducks and found 88% carrying C. jejuni subsp.…”
Section: Introductionmentioning
confidence: 99%
“…Campylobacter spp. are also natural inhabitants of the intestinal tract of many animals and birds (Skirrow 1990;Park et al 1991;Skirrow 1994;Stern et al 1995). Helicobacter pullorum has been implicated in human diarrhoea and as a cause of vibrionic hepatitis in chickens (Burnens et al 1994(Burnens et al , 1996.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, a reduction in the numbers of campylobacters entering the human food chain is likely to have a beneficial effect on the disease burden. In particular, the rearing of broiler chickens is a prime target for intervention with bacteriophages, given the reported scale of Campylobacter colonization of broilers (12) and the relatively large numbers of campylobacters present in the gastrointestinal tract and secreted by colonized birds (31). As a first step toward implementing these strategies, we sought to establish whether bacteriophages were already present on retail poultry in order to gauge the possible impact of intervention and to establish whether these strategies would introduce any new biological elements into the human food chain.…”
mentioning
confidence: 99%
“…Stern et al reported that transportation and holding increase Campylobacter carcass contamination in broilers (28). In their study, Campylobacter was detected on 12.1% of carcasses of broilers that were slaughtered on the farm (average ϭ log 10 2.71 Campylobacter spp.…”
mentioning
confidence: 96%